THE ROLE OF PARODY IN POSTMODERN LITERATURE (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT The study of the role played in parody in modernist art, literature and theory made in Rose's Parody/meta-fiction (1979) is extended in this article to a study of the contrasting roles attributed to reflexive parody in post-modernism by Fredric Jameson (1984) and Charles Jencks (1986). Firstly Jameson's claim that modern reflexive parody has ‘degenerated’ into an unreflexively form of pastiche in post-modernism is criticized and contrasted with Jencks' criticisms of the characterization of post-modernist art as pastiche. Secondly, it is argued with Jencks that many post-modernist works contain a number of dual or multiple coding’s, and it is suggested that these are also characteristic of a new development of the reflexive parody found in modernism. Finally it is argued that if modernist parody would be transcended in post-modernism as an outdated modernist from as Jameson suggests, then particle must also be as ripe for such a transcendence given that it too is as old as the modernist parody which Jameson sees it as replacing, but that the most likely scenario for the immediate future will be that both parody and pastiche will be given new functions by their post-modernist owners, and that these new functions will continue to co-exist with the older forms of parody still being used by modernist writers and artists.